Inhibition of the TRIM24 bromodomain reactivates latent HIV-1 - Riley M. Horvath; Zabrina L. Brumme; Ivan Sadowski (Scientific Reports, 2023)
Abstract Expression of the HIV-1 genome by RNA Polymerase II is regulated at multiple steps, as are most cellular genes, including recruitment of general transcription factors and control of transcriptional elongation from the core promoter. We recently discovered that tripartite motif protein TRIM24 is recruited to the HIV-1 Long Terminal Repeat (LTR) by interaction with TFII-I and causes transcriptional elongation by stimulating association of PTEF-b/ CDK9. Because TRIM24 is required for stimulation of transcription from the HIV-1 LTR, we were surprised to find that IACS-9571, a specific inhibitor of the TRIM24 C-terminal bromodomain, induces HIV-1 provirus expression in otherwise untreated cells. IACS-9571 reactivates HIV-1 in T cell lines bearing multiple different provirus models of HIV-1 latency. Additionally, treatment with this TRIM24 bromodomain inhibitor encourages productive HIV-1 expression in newly infected cells and inhibits formation of immediate latent transcriptionally repressed provirus. IACS-9571 synergizes with PMA, ionomycin, TNF-α and PEP005 to activate HIV-1 expression. Furthermore, co-treatment of CD4 + T cells from individuals with HIV-1 on antiretroviral therapy (ART) with PEP005 and IACS-9571 caused robust provirus expression. Notably, IACS-9571 did not cause global activation of T cells; rather, it inhibited induction of IL2 and CD69 expression in human PBMCs and Jurkat T cells treated with PEP005 or PMA. These observations indicate the TRIM24 bromodomain inhibitor IACS-9571 represents a novel HIV-1 latency reversing agent (LRA), and unlike other compounds with this activity, causes partial suppression of T cell activation while inducing expression of latent provirus.